2010
DOI: 10.1007/s10886-010-9754-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Sex Pheromone of the Spruce Seed Moth, Cydia strobilella L.

Abstract: The spruce seed moth, Cydia strobilella L., is a serious pest on cones of spruce (Picea spp.) in the Holarctic region. Previous studies from different parts of its area of distribution have reported conflicting results on the composition of its sex pheromone. By gas chromatography with electroantennographic detection, coupled gas chromatography-mass spectrometry, a Y-tube olfactometer bioassay, and field trials, the sex pheromone of Swedish populations of the species was identified as (8E,10E)-dodecadienyl ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 19 publications
1
25
2
Order By: Relevance
“…After the first half of the flight season, when no moths had been caught in the traps, one set of traps in Maltesholm was baited with a sub-optimal pheromone lure for C. strobilella (Wang et al, 2010). We used red rubber septa (11 mm × 5 mm, #224100-020 from Wheaton Science Products, Millville, NJ, USA) as dispenser, and applied 100 µl of pheromone solution, which contained 6 ng each of (E,E)-8,10-dodecadienyl acetate (E8,E10-12:OAc) and (E,Z)-8,10-dodecadienyl acetate (E8,Z10-12:OAc), i.e., a much lower dose compared to what has previously been used in field trials on this species (Wang et al, 2010;Svensson et al, 2013).…”
Section: Behavioural Field Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the first half of the flight season, when no moths had been caught in the traps, one set of traps in Maltesholm was baited with a sub-optimal pheromone lure for C. strobilella (Wang et al, 2010). We used red rubber septa (11 mm × 5 mm, #224100-020 from Wheaton Science Products, Millville, NJ, USA) as dispenser, and applied 100 µl of pheromone solution, which contained 6 ng each of (E,E)-8,10-dodecadienyl acetate (E8,E10-12:OAc) and (E,Z)-8,10-dodecadienyl acetate (E8,Z10-12:OAc), i.e., a much lower dose compared to what has previously been used in field trials on this species (Wang et al, 2010;Svensson et al, 2013).…”
Section: Behavioural Field Trialsmentioning
confidence: 99%
“…We used red rubber septa (11 mm × 5 mm, #224100-020 from Wheaton Science Products, Millville, NJ, USA) as dispenser, and applied 100 µl of pheromone solution, which contained 6 ng each of (E,E)-8,10-dodecadienyl acetate (E8,E10-12:OAc) and (E,Z)-8,10-dodecadienyl acetate (E8,Z10-12:OAc), i.e., a much lower dose compared to what has previously been used in field trials on this species (Wang et al, 2010;Svensson et al, 2013). E8,Z10-12:OAc was synthesized by Dr. Ilme Liblikas, University of Tartu, Estonia.…”
Section: Behavioural Field Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that the sex pheromone components of China populations of H. robusta were different from other regions. However, the phenomenon of (Qingyuan, Guangdong, China, 2014) insect sex pheromone variation is universal, such as Hemileuca electra (McElfresh and Millar 1999), Hyphantria cunea (Su et al 2008), genus Adoxophyes (Yang et al 2009), Cydia strobilella (Wang et al 2010), Spodoptera frugiperda (Unbehend et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The single headspace sample used as stimulus for recordings was collected from spruce flowers in mid May, the peak of the flight season of C. strobilella (Wang et al, 2010;Svensson et al, 2013), using the same method as described above. and 0.25 lm film thickness; J&W Scientific).…”
Section: Mothsmentioning
confidence: 99%